Epileptiform activity and spreading depolarization in the blood-brain barrier-disrupted peri-infarct hippocampus are associated with impaired GABAergic inhibition and synaptic plasticity - Lippmann, Kristina; Kamintsky, Lyn; Kim, Soo Young; Lublinsky, Svetlana; Prager, Ofer; Nichtweiss, Julia Friederike; Salar, Seda; Kaufer, Daniela; Heinemann, Uwe; Friedman, Alon (Journal of Cerebral Blood Flow and Metabolism, 2017)
Peri-infarct opening of the blood-brain barrier may be associated with spreading depolarizations, seizures, and epileptogenesis as well as cognitive dysfunction. We aimed to investigate the mechanisms underlying neural network pathophysiology in the blood-brain barrier-dysfunctional hippocampus. Photothrombotic stroke within the rat neocortex was associated with increased intracranial pressure, vasogenic edema, and peri-ischemic blood-brain barrier dysfunction that included the ipsilateral hippocampus. Intrahippocampal recordings revealed electrographic seizures within the first week in two-thirds of animals, accompanied by a reduction in gamma and increase in theta frequency bands. Synaptic interactions were studied in parasagittal hippocampal slices at 24 h and seven days post-stroke. Field potential recordings in CA1 and CA3 uncovered multiple population spikes, epileptiform episodes, and spreading depolarizations at 24 h. Input-output analysis revealed that fEPSP-spike coupling was significantly enhanced at seven days. In addition, CA1 feedback and feedforward inhibition were diminished. Slices generating epileptiform activity at seven days revealed impaired bidirectional long-term plasticity following high and low-frequency stimulation protocols. Microarray and PCR data confirmed changes in expression of astrocyte-related genes and suggested downregulation in expression of GABA A -receptor subunits. We conclude that blood-brain barrier dysfunction in the peri-infarct hippocampus is associated with early disinhibition, hyperexcitability, and abnormal synaptic plasticity.
Created from Fastlane, Scopus look-up
Keywords: Blood-brain barrier; hippocampus; inhibition; seizures; synaptic plasticity